(untitled) (Research, Society and Development, 2022)
The pandemic of COVID-19 increased the need for the use of digital tools in teaching activities, in order to follow up on academic activities and provide opportunities for interaction between teachers and students. Objective: To report the experience of the academic monitoring of the module of the Teaching, Service and Community Integration Program II (PIESC 2), of the medical course, mediated by digital tools. Method: Descriptive study, with a qualitative approach and of the experience report type. The remote and synchronous meetings to offer the monitoring were held weekly. "Google Forms", "Canva", "Mentimeter" and "Classroom" were used as fundamental interactive resources for planning and applying the activities. Results: From the perspective of the student-monitors, there was a need to adapt to the new reality imposed, being necessary the adaptation of the activities to the remote modality. Through digital tools, it was possible to give reviews, conduct questionnaires, and solve doubts in a synchronous and efficient way. The challenges arising from the period enabled the development of academic and professional skills. From the students’ perspective, the proposal was successfully accomplished, since it allowed the consolidation of the theoretical and practical knowledge proposed by the module. Conclusion: The use of digital tools showed significant contributions, given the pandemic scenario, configured as a way to face and adapt to the new imposed reality, narrowing bonds and adding knowledge to all those who contributed to the ethical and committed operation of the program and, still consolidates its relevance in the context of higher education.